2011
DOI: 10.1002/smi.1409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neuroticism, Extraversion and Openness on Stress Responses

Abstract: The present research moved beyond focusing on negative dispositions to investigate the influence of positive aspects of personality, namely extraversion and openness, on stress responses including appraisals, affect and task performance. Challenge appraisals occur when stressor demands are deemed commensurate with coping resources, whereas threat appraisals occur when demands are believed to outweigh coping resources. We examined the unique influence of personality on stress responses and the mediating role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
120
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 37 publications
19
120
3
4
Order By: Relevance
“…In order to understand and explain the relationship between neuroticism and emotional exhaustion it is necessary to examine the structure and nature of both constructs. Individuals high in neuroticism are prone to tension, worry and apprehension, tend to cope poorly with stress, and have a tendency to view events as threatening or problematic (Schneider et al, 2012;Watson et al, 1994). According to the transactional model, the tendency to appraise workplace demands as threats rather than challenges is an important step in the process leading to the development of stress.…”
Section: Predictors Of Emotional Exhaustionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to understand and explain the relationship between neuroticism and emotional exhaustion it is necessary to examine the structure and nature of both constructs. Individuals high in neuroticism are prone to tension, worry and apprehension, tend to cope poorly with stress, and have a tendency to view events as threatening or problematic (Schneider et al, 2012;Watson et al, 1994). According to the transactional model, the tendency to appraise workplace demands as threats rather than challenges is an important step in the process leading to the development of stress.…”
Section: Predictors Of Emotional Exhaustionmentioning
confidence: 98%
“…Kokkinos (2007) for example, identified neuroticism as a significant positive predictor of all three burnout dimensions in a sample of Cypriot teachers, while Cano-Garcia, Padilla-Munoz, and CarrascoOrtiz (2005) found neuroticism to significantly and positively predict emotional exhaustion among a Spanish sample. Neuroticism has been found to predict higher threat appraisals, a key step in the stress development process (Schneider, Rench, Lyons, & Riffle, 2012). The tendency of people with high levels of neuroticism to express more negative emotions, emotional instability and stress reactions appears to render such individuals vulnerable to burnout and other psychological disturbances (Watson, Clark, & Harkness, 1994).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Secondly, outgoing individuals tend to pay attention to positive stimulation (Derryberry & Reed, 1994;Huang & Luo, 2006), which almost happens automatically Huang & Luo, 2007). Similarly, studies have shown that high extraversion and life satisfaction are correlated, and extroversion can improve SWB (McCrae & John, 1992); high extraversion and job stress and burnout were significantly negatively correlated (Mills & Huebner, 1998;Bakker , Zee & Lewig, 2006); extraversion has a positive effect on stress response (Chu et al, 2015;Schneider, 2012). discover the underlining mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This trait involving an energetic approach towards the world and the need for companionship should bring beneficial effects in difficult situations (Schneider et al, 2011). However, research findings concerning extraversion are inconsistent, and in earlier studies this trait was found to be unrelated to cognitive appraisal (Penley & Tomaka, 2002).…”
Section: Discussionmentioning
confidence: 99%